Trends in the prevalence of elevated cardiovascular risk and the control of its risk factors Among US adults, 2001–2020 - Huang, Haitao; Liu, Jianhong; Liang, Xiao; Fang, Lingyan; Yang, Chenhui; Ke, Kangling; Bai, Hemanyun; Xu, Weize; Li, Weiyan; Meng, Fanji; Chen, Can (Frontiers in Cardiovascular Medicine, 2023)
Background: An accurate assessment of current trends in cardiovascular risks could inform public health policy. This study aims to determine 20-year trends in the prevalence of elevated cardiovascular risk and its risk factors’ control among US adults. Methods: In this serial cross-sectional analysis of 23,594 adults, aged 40–79 years, without clinical atherosclerotic cardiovascular disease (ASCVD) in the National Health and Nutrition Examination Survey from 2001 to 2020, we calculated the prevalence of elevated cardiovascular risk (10-year ASCVD risk ≥ 7.5%) for all participants and subgroups with their risk factors controlled for diabetes, hypertension, or dyslipidemia. Results: The age- and sex-adjusted prevalence of elevated cardiovascular risk slightly decreased from 41.5% (95% CI, 39.7–43.3%) in 2001–2004 to 38.6% (95% CI, 36.1–41.1%) in 2017–2020 (P for trend = 0.169) while the respective sex-adjusted prevalence significantly increased from 34.4% (95% CI, 32.8–36.0%) to 39.5% (95% CI, 37.0–42.0%; P for trend < 0.001). Sex and race continued to show disparities in cardiovascular risk. Furthermore, a worsening disparity in age- and sex-adjusted prevalence of elevated cardiovascular risk between young and old and a narrowing gap among different education and poverty index levels (all P trend for interaction < 0.05). Differential decomposition analysis found that demographic changes (primarily population aging) led to an 8.8% increase in the prevalence of elevated cardiovascular risk from 2001–2004 to 2017–2020, while risk factor control led to a 3.8% decrease. The rate of individuals receiving treatment for diabetes, hypertension, or dyslipidemia increased significantly between 2001 and 2020 (all P for trend < 0.05). The rate of participants with hypertension who achieved blood pressure under 130/80 mmHg and those with dyslipidemia who achieved a non-high-density lipoprotein cholesterol level under 130 mg/dL increased significantly (all P for trend < 0.001). Conclusions: There is a slight reduction in the prevalence of age- and sex-adjusted elevated cardiovascular risk among US adults without clinical ASCVD between 2001 and 2020, while the sex-adjusted prevalence significantly increased. The decrease in elevated cardiovascular risk prevalence was mainly attributed to risk factor control, while demographic changes contributed to an increase.